2013
DOI: 10.1007/s12288-013-0240-9
|View full text |Cite
|
Sign up to set email alerts
|

Rational Use of Recombinant Factor VIIa in Clinical Practice

Abstract: In the United States, the FDA-approved indications for recombinant factor VIIa is for bypassing inhibitors to factors VIII and IX in patients with hemophilia A and B respectively and for treatment of congenital factor VII deficiency. In European countries, rFVIIa is licensed for the above indications as well as for Glanzmann's thrombasthenia. In absence of high-quality data favoring off-label use of this agent and laboratory test to predict response to this agent, and in view of high cost of rFVIIa, off-label … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 27 publications
1
20
0
Order By: Relevance
“…Thrombosis is one of the most serious complications. However, it has been shown that even high doses as 346 mcg/kg may be well tolerated in hemophilic patients . The reported incidence of thromboembolic event ranged from 1% to 2% up to 9.8% .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thrombosis is one of the most serious complications. However, it has been shown that even high doses as 346 mcg/kg may be well tolerated in hemophilic patients . The reported incidence of thromboembolic event ranged from 1% to 2% up to 9.8% .…”
Section: Discussionmentioning
confidence: 99%
“…6,8,9 It is not associated with the risk of blood-transmitted diseases, as a recombinant product is not derived from human or animal plasma. 10 Thrombosis is one of the most serious complications. However, it has been shown that even high doses as 346 mcg/kg may be well tolerated in hemophilic patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, we chose to use recombinant factor VIIa (rFVIIa), a synthetic hemostatic agent originally used to treat bleeding in hemophilia A patients who had developed inhibitors to factor VIII [22,23]. Given its integral effect of coagula- tion function, rFVIIa has also been used to treat bleeding of various other etiologies in many clinical scenarios.…”
Section: Discussionmentioning
confidence: 99%
“…Recombinant activated FVII (rFVIIa) has been approved for the treatment of hemophilia and congenital FVII deficiency, and can also restore coagulopathy in traumatic or postoperative bleeding and postpartum hemorrhage (Dutta and Verma 2014). Several mammalian cell lines including HEK293 human embryonic kidney, Chinese hamster ovary, and baby hamster kidney cells have been used to synthesize recombinant FVII and other vit.K-dependent proteins (Bohm et al 2015); however, as the yield is low, a more efficient large-scale culture system is needed.…”
Section: Introductionmentioning
confidence: 99%